Pretreatment with platelet-rich plasma protects against ischemia-reperfusion induced flap injury by deactivating the JAK/STAT pathway in mice - Linlin Su; Songtao Xie; Ting Li; Yanhui Jia; Yunchuan Wang (BMC, 2024)
Abstract Background Ischemia-reperfusion (I/R) injury is a major cause of surgical skin flap compromise and organ dysfunction. Platelet-rich plasma (PRP) is an autologous product rich in growth factors, with tissue regenerative potential. PRP has shown promise in multiple I/R-induced tissue injuries, but its effects on skin flap injury remain unexplored. Methods We evaluated the effects of PRP on I/R-injured skin flaps, optimal timing of PRP administration, and the involved mechanisms. Results PRP protected against I/R-induced skin flap injury by improving flap survival, promoting blood perfusion and angiogenesis, suppressing oxidative stress and inflammatory response, and reducing apoptosis, at least partly via deactivating Janus kinase (JAK)-signal transducers and activators of transcription (STAT) signalling pathway. PRP given before ischemia displayed overall advantages over that given before reperfusion or during reperfusion. In addition, PRP pretreatment had a stronger ability to reverse I/R-induced JAK/STAT activation and apoptosis than AG490, a specific inhibitor of JAK/STAT signalling. Conclusions This study firstly demonstrates the protective role of PRP against I/R-injured skin flaps through negative regulation of JAK/STAT activation, with PRP pretreatment showing optimal therapeutic effects.